Properties of modified bitumen in hot mix asphalt using local crumb rubber - Lim, Min Khiong (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This thesis presents a study of laboratory evaluation on the properties of modified bitumen in Hot Mix Asphalt (HMA) using local crumb rubber with the aim of partially replacing bituminous binder as well as improving the binder’s properties. In the study, fine crumb rubber ranging of 0.3mm to 0.6mm taken from waste tires was added into bituminous binder using the wet process. The crumb rubber content of 5%, 10% 15% and 19% of weight of bitumen were added to virgin binder as modified specimens while unmodified bitumen shall be used as control samples. The crumb rubber modified binder specimens were examined by the penetration test and softening test to define the changes in terms of their physical properties prior to mix with graded aggregates to determine the volumetric properties such as Voids in Total Mix (VIM), Voids in Mineral Aggregate (VMA) and Voids Filled with Bitumen) VFB. Apart from that the Marshall Stability, Marshall Flow and Stiffness shall be determined. Two HMA aggregate mixes were being considered in this study, namely AC 14 (dense graded) and SMA 14 (gap graded). The outcome indicated that the modified binder posed a higher viscosity and temperature resistant while the increase of crumb rubber content lead to the increase in terms of the performance of HMA characteristic especially the Marshall Stability for both HMA mixes.